Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Buckland Fire Scar, Alaska - Tabea Rettelbach; Ingmar Nitze; Inge Grünberg; Jennika Hammar; Simon Schäffler; Daniel Hein; Matthias Gessner; Tilman Bucher; Jörg Brauchle; Jörg Hartmann; Torsten Sachs; Julia Boike; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 7 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates six data subsets of the Buckland fire scar, Alaska, covering approximately 45 km^2. All images were collected on 26 June 2021.